Measurement of the inclusive W and Z production cross sections in pp collisions at root s = 7 TeV with the CMS experiment - Chatrchyan, S. (2011)
A measurement of inclusive W and Z production cross sections in pp collisions at root s = 7 TeV is presented. The electron and muon decay channels are analyzed in a data sample collected with the CMS detector at the LHC and corresponding to an integrated luminosity of 36 pb(-1). The measured inclusive cross sections are sigma(pp -> WX) x B(W -> lv) = 10.31 +/- 0.02 (stat.) +/- 0.09 (syst.) +/- 0.10 (th.) +/- 0.41 (lumi.) nb and sigma(pp -> ZX) x B(Z -> l(broken vertical bar) l(-)) = 0.974 +/- 0.007 (stat.) +/- 0.007 (syst.) +/- 0.018 (th.) +/- 0.039 (lumi.) nb, limited to the dilepton invariant mass range 60 to 120 GeV. The luminosity-independent cross section ratios are (sigma(pp -> WX) x B(W -> lv)) / (sigma(pp -> ZX) x B(Z -> l(+)l(-))) = 10.54 +/- 0.07 (stat.) +/- 0.08 (syst.) +/- 0.16 (th.) and (sigma(pp -> W+ X) x B(W+ -> l(+) v)) / (sigma(pp -> W- X) x B(W- -> l(-) (v) over bar)) = 1.421 +/- 0.006 (stat.) +/- 0.014 (syst.) +/- 0.029 (th.). The measured values agree with next-to-next-to-leading order QCD cross section calculations based on recent parton distribution functions.